AQUEOUS EXTRACT OF BALINESE PURPLE SWEET POTATO (IPOMOEA BATATAS L.) PREVENTS OXIDATIVE STRESS AND DECREASES BLOOD INTERLEUKIN-1 IN HYPERCHOLESTEROLEMIC RABBITS - Jawi, I M.; Indrayani, A. Wiwiek; Sutirta-Yasa, I W. P. (BALI MEDICAL JOURNAL, 2015)
Background: Hypercholesterolemia can cause oxidative stress, endothelial dysfunction and atherosclerosis. Anthocyanin can prevent oxidative stress, it will decrease the inflammation by decreasing the pro inflammatory cytokine in animal models. Purple sweet potato in Bali has been proven of having high anthocyanins content. The aim of these study was to prove the ability of aqueous extract of Balinese purple sweet potato (Ipomoea batatas L.) in decreasing the blood interleukin-1 level in hypercholesterolemic rabbits. Methods: Subjects of this study were 18 male adult rabbits divided into 3 groups with randomized post test only control group design. Group 1 rabbits were given standard diet as a control group. Group 2 rabbits were given high cholesterol diet. Group 3 rabbits were given aqueous extract of Balinese purple sweet potato 4 ml/Kg.BW/day and high cholesterol diet. After 60 days of treatment, the blood level of total cholesterol, MDA and interleukin- 1 were measured as post test examination. The data were analysed by using anova. Results: The results showed significant increases of blood total cholesterol, MDA, and interleukin-1 in group 2 (p